Os Lugares Invisíveis - Leite, Maria Angela Faggin Pereira (Paisagem e Ambiente, 1998)
In Brazil in the former 40 years, developmental debate and specialy the liberalistic debate have always tried to justify the replacem ent of a communitarian way of life for an individual behaviour pattern that inhibits the emergence of solidarity. Based upon these ideas, som e public program s of spatial intervention, in spite of their intention of representing the hole territory, frequently operates just in a few places where visibility assure some control power in the organization of the territory, worsen the problems of fragmentation and individualism